Navigating HIV self-testing: Concerns among adolescents and young people aged 15–24 years in Uganda. An exploratory qualitative study - Richard Muhumuza; Denis Ndekezi; Rehema Nagawa; Esther Awino; Chiti Bwalya; Madalitso Mbewe; Joanita Nassali; Jackline Namara; Felix Rutaro; Musonda Simwinga; Virginia Bond; Janet Seeley; et al. (PLoS ONE, 2026)
Introduction HIV self-testing (HIVST) has the potential to overcome barriers to conventional clinic-based HIV testing services by offering a convenient, private, and confidential way to test. This study aimed to explore the concerns about HIV self-testing among adolescents and young people (AYP) aged 15–24 years in Uganda, where HIV self-testing is still not widely available. Methods This exploratory qualitative study conducted 14 audio-recorded in-depth interviews and six focus group discussions with adolescents and young people in Wakiso district, Uganda, between March 2021 to February 2022. These interviews were transcribed verbatim and analysed thematically using the socio-ecological model. All participants provided written informed consent and assent before participating in the study. Results AYP viewed HIVST as a potentially helpful and acceptable testing method. However, several concerns emerged and these are presented using five themes. At the individual level, participants expressed fear of suicidal thoughts if one tested HIV positive, lack of adequate information, anticipated increased risky sexual behaviours, neglect of other HIV preventive measures, and misinterpretation of test kit results. Interpersonal concerns were centred on partner violence, parental coercion, and social rejection. At the community level, participants noted the potential for stigma, unintended pregnancies, and discrimination. Institutional concerns focused on the lack of referral services and inadequate counselling following HIV self-testing. At the structural level, limited accessibility for persons with disabilities was a key concern. Conclusion While AYP have established that HIVST is essential, various concerns need to be addressed to improve its acceptability, up-take and utilisation. Providing more explicit information about the testing procedure, clarifying any misinterpretation of results, and providing easy access to counselling services, especially at distribution points, is crucial towards guaranteeing the effective roll-out of HIVST among young people. Special attention must also be given to marginalised populations, including people living with disabilities, to ensure fairness in their access and utilisation of services. Implementation of all this will be crucial towards maximising the potential benefits of HIVST in Uganda’s HIV prevention efforts.